Doktrin Kristus dalam Teologi Sistematika: Sifat, Karya, dan Relevansinya - Hanti Hanti; Lira Oktoratilova; Meisy Cahyanti; Sarmauli Sarmauli (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This library research examines the doctrine of Christ (Christology) in systematic theology, focusing on the union of His divinity and humanity, His work of salvation, and its relevance for contemporary believers. The study aims to provide a systematic understanding of Christ's identity and work based on biblical foundations and historical church confessions, such as the Councils of Nicaea and Chalcedon. The findings indicate that the orthodox understanding of Christ as true God and true man is the foundational pillar for soteriology and Christian life. His work of salvation through substitutionary atonement and resurrection achieves redemption, reconciliation, and life transformation. Furthermore, this doctrine has significant practical relevance, serving as a basis for personal faith, strengthening church teaching and mission, and providing ethical guidance in modern societal contexts. A correct understanding of Christology is crucial to fortify faith against theological error and to live out a Christ-centered life.